(3GdMQha GdYQHjI Hjf GdMPa hGdJbOjQ (B: s (3OQGSI fMhjI OdGdjI (B/ s - (3QeVGf QHjY NVQi SdjeGf s; (3ShRGf agei (B: s; (3UdGM QhGi (B: s ((3GdbGgQI (B: s (3QeVGf QHjY NVQi SdjeGf (B: s, 2011)
(3JJfGhd GdQSGdI (B( (3GdMQha GdYQHjI (B) (3GdMPa hGdJbOjQ ai Jdc GdMQha eHfGgG heYfGgG hgi OQGSI fMhjI OdGdjI hbO YQV GdHGMK XGgQI GdMPa heGjJYdb HgG ef JYQja ddMPa hHjGf ecGfJg hCSHGHg hOhGYjg hGdTQhW hGdVhGHW GdJi jLH JhGaQgG ai GdeMPha hHjGf Ci GdMQha Chdi HGdMPa ef ZjQg hCfhGY GdMPa ai Jdc GdMQha hPcQ GdBQGA GdefGOjI HEfcGQ Pdc GdMPa ai Jdc GdMQha hGdQO YdjgG HeG dG jOY eLGdG ddTc ai hLhOI hGdbhd Hg (B: (3cd Pdc Je JfGhdI s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI OGQ GdYdhe (B- (3bSe GdfMh hGdUQa hGdYQhVs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdJbOjQ s; (3GdMPa s; (3GdMQha s